ERP-Systeme Architektur, Management und Funktionen des Enterprise Resource Planning - Gronau, Norbert 1964- (De Gruyter Oldenbourg, 2021)
ERP systems continue to be essential for companies of all sizes and kinds in significantly boosting productivity. Based on extensive experience gained from research and consulting projects, this book provides a vendor-neutral discussion of a range of ERP system functions. The fourth edition has been revised, updated, and corrected for use as a textbook
Keywords: ERP.; Enterprise Resource Planning; Industrie 4.0; Wirtschaftsinformatik; BUSINESS & ECONOMICS / Information Management; Enterprise-Resource-Planning